2000
DOI: 10.1200/jco.2000.18.7.1399
|View full text |Cite
|
Sign up to set email alerts
|

Exemestane Is Superior to Megestrol Acetate After Tamoxifen Failure in Postmenopausal Women With Advanced Breast Cancer: Results of a Phase III Randomized Double-Blind Trial

Abstract: EXE prolongs survival time, time to tumor progression, and time to treatment failure compared with MA and offers a well-tolerated treatment option for postmenopausal women with progressive advanced breast cancer who experienced failure of tamoxifen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
196
0
12

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 497 publications
(214 citation statements)
references
References 20 publications
6
196
0
12
Order By: Relevance
“…All patients taking part in these trials had chemotherapy-resistant EOC and therefore represent a group with a poor prognosis. Similar results were reported in breast cancer patients with visceral metastases who received anastrazole (RR, 7%-14%) or exemestane (RR, 13.5%-25%) [82][83][84][85]. Endocrine treatment in breast cancer is generally more beneficial for patients with soft tissue metastases or low-volume disease.…”
Section: Discussionsupporting
confidence: 72%
“…All patients taking part in these trials had chemotherapy-resistant EOC and therefore represent a group with a poor prognosis. Similar results were reported in breast cancer patients with visceral metastases who received anastrazole (RR, 7%-14%) or exemestane (RR, 13.5%-25%) [82][83][84][85]. Endocrine treatment in breast cancer is generally more beneficial for patients with soft tissue metastases or low-volume disease.…”
Section: Discussionsupporting
confidence: 72%
“…Another compassionate-use study in Belgium has reported that 26.4% of patients with VM achieved CB following fulvestrant treatment [15]. With regard to exemestane, a previous Phase III trial evaluating this agent versus megestrol acetate found that CB rates were higher with exemestane (36.3%) than with megestrol acetate (30.0%) in patients with VM, although the difference was not significant [4]. In addition, a recent case series where exemestane was given following several prior therapies, including non-steroidal AIs, described a CB rate of 33.0% for patients with visceral involvement [10].…”
Section: Discussionmentioning
confidence: 99%
“…In a subgroup analysis of combined data from these trials, both agents demonstrated similar activity in patients with VM, with objective response and clinical benefit (CB) endpoints favouring fulvestrant, although the differences between treatments were not statistically significant [6]. In another double-blind, randomised Phase III trial comparing exemestane versus megestrol acetate (Megace TM ) after tamoxifen failure, exemestane demonstrated better activity than megestrol acetate in patients with VM [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9,10]. Kituose veikaluose [11,12] aprašyta, kad, šios grupės pacientams skyrus hormonų terapiją AI, periodas iki progresavimo buvo ilgas.…”
Section: Svarstymasunclassified